2021
DOI: 10.1530/joe-20-0428
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mineralisation in bone and vascular tissue: a comparative review

Abstract: Biomineralisation, the deposition of mineral onto a matrix, can be both a physiological and pathological process. Bone formation involves the secretion of an extracellular matrix (ECM) by osteoblasts and subsequent mineralisation of that matrix. It is regulated by a number of local and systemic factors and is necessary for maintenance of normal bone health. Conversely, mineralisation (or calcification) of soft tissues, including the vasculature, is detrimental to that tissue, leading to diseases such as arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 156 publications
0
36
0
Order By: Relevance
“…In bone, type I collagen comprises approximately 80% of the total proteins [ 36 ] and collagen fibrils serve to deposit Ca 2+ and P i to form hydroxyapatite crystals within their 40 nm holes [ 37 ]. The Ca 2+ and P i are presumably released from the extracellular matrix vesicles in which Ca 2+ and P i ions, enzymes, lipids, and miRNAs are enriched [ 38 ]. Furthermore, no change in OCN expression could be detected after BMP-2 exposure compared to the control, indicating an immature state in mineralization, since osteocalcin promotes the deposition of minerals in the extracellular matrix [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In bone, type I collagen comprises approximately 80% of the total proteins [ 36 ] and collagen fibrils serve to deposit Ca 2+ and P i to form hydroxyapatite crystals within their 40 nm holes [ 37 ]. The Ca 2+ and P i are presumably released from the extracellular matrix vesicles in which Ca 2+ and P i ions, enzymes, lipids, and miRNAs are enriched [ 38 ]. Furthermore, no change in OCN expression could be detected after BMP-2 exposure compared to the control, indicating an immature state in mineralization, since osteocalcin promotes the deposition of minerals in the extracellular matrix [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mineralization can also occur in an uncontrolled or pathological manner in many soft tissues including cardiovascular, kidney and articular cartilage leading to morbidity and mortality. Recent studies focused on the underlying mechanisms for vascular calcification have shown that components regulating physiological mineralization are also present in areas of pathological mineralization (Bourne, Wheeler-Jones, & Orriss, 2021; Tesfamariam, 2019), suggesting that mechanisms for pathological mineralization may be a recapitulation of what happens during normal development. Therefore, studies focused on the understanding of regulatory molecules and cellular processes involved in ossification of cartilage and bone tissues during normal development may provide important clues toward the understanding of components involved in pathological mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, an often overlooked aspect should be emphasized, when it comes to bone dysfunctions, namely the crucial importance of an efficient blood supply to the whole body thanks to an optimal circulation. As recently reported, the accumulation of calcium-phosphate crystals (i.e., HA) in the arterial wall as well as in cardiac valves has a significant impact on morbidity and mortality in several diseases such as CKD, osteoporosis, and diabetes patients by provoking severe cardiovascular events [ 102 ]. Interestingly, these pathological conditions are the same in which bone loss is also present.…”
Section: Discussionmentioning
confidence: 99%